2021
DOI: 10.46792/fuoyejet.v6i2.644
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antimicrobial Properties of Eucalyptus torelliana Oils

Abstract: Normal oil and Essential oil from fresh leaves of Eucalyptus torelliana (F. Muell) were extracted using solvent (Soxhlet) and steam distillation extraction methods respectively. The leaves were screened for the presence of secondary metabolites and the extracted oils for their antimicrobial potentials. The phytochemical screening revealed the presence of Phytates (27.81 mg/g) Phytic acids (7.833mg/g) Oxalates (3.061mg/g) Tannins (2.457mg/g) Phenols (30.00%) Flavonoids (2.948%) Saponins (3.166%) and Alkaloids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Meanwhile, pertaining eucalyptus leaves, this work shows that, the leaves contain phytoconstituents (Table 3) similar to the works related by Kaur et al, (2019); Adekoya & Akeem (2021). Kaur etal., (2021) showed that, the plant possesses the ability to act against certain microbes (an indication of phytochemistry effectiveness).…”
Section: Resultssupporting
confidence: 86%
“…Meanwhile, pertaining eucalyptus leaves, this work shows that, the leaves contain phytoconstituents (Table 3) similar to the works related by Kaur et al, (2019); Adekoya & Akeem (2021). Kaur etal., (2021) showed that, the plant possesses the ability to act against certain microbes (an indication of phytochemistry effectiveness).…”
Section: Resultssupporting
confidence: 86%